Nonuniform estimates in the approximation by the Poisson law - Padvelskis, Kazimieras (Lietuvos matematikos rinkinys, 2023)
Poisson approximation for the sum of independent random variables is investigates in this paper.
Keywords: Poisson distribution; independent random variables; nonuniform estimates